STRATEGI GURU MENGHADAPI TRANSISI KURIKULUM 13 KE KURIKULUM MERDEKA: Strateguru Menghadapi Transisi Kurikukum 13 Ke Kurikulum Merdeka - ANGELA, MEIZI (Journal Education And Islamic Studies, 2025)
The transition from the 2013 Curriculum to the Merdeka Curriculum at SDN Semangat Dalam 3 presents several significant challenges for the school. These changes include modifications to the assessment system from Minimum Completeness Criteria (KKM) to Learning Objective Achievement Criteria (KKTP), variations in learning models, and the implementation of the Pancasila Student Profile Reinforcement Project (P5), all of which require careful adjustment. Teachers face obstacles such as students being less accustomed to critical thinking, limited access to learning media, and the need for more effective teaching methods. Furthermore, the consistent implementation of the Merdeka Curriculum in the Barito Kuala region is still not optimal. This research plays a crucial role in understanding how schools overcome challenges related to curriculum transition, especially in areas that may not be fully prepared for these changes. Using a descriptive qualitative research method, this study employs techniques such as interviews, observations, and documentation. Its primary objective is to identify the strategies implemented by the school to address these barriers and to assess the effectiveness of the approaches used. The strategies adopted by the school, such as utilizing government assistance, diagnostic assessments, developing learning models, and active teacher participation in learning communities, have proven effective in facilitating curriculum adaptation. Continuous support and enhancement of teacher competence are essential for optimal implementation of the Merdeka Curriculum and improving the quality of learning.